Joining of Composite Materials 1981
DOI: 10.1520/stp33480s
|View full text |Cite
|
Sign up to set email alerts
|

Design Data for Graphite Cloth Epoxy Bolted Joints at Temperatures up to 450 K

Abstract: Results of a design data development program involving hundreds of graphite epoxy bolted joint tests are summarized. Emphasis was on obtaining information for HMF330C/34 cloth material at room temperature, 394, and 450 K; however, many specimens made from T300/5208 and AS/3501 tape laminates were tested to provide correlating information on bearing behavior and the importance of hole-bolt tolerances. Bearing strengths for quasi-isotropic laminates made from these three prepregs were similar. Complete removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Although bolt-bearing tests have been conducted by many investigators in the past [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], limited data were available to fairly assess the validity of the 3-D model and the computer code, 3DBOLT/ABAQUS. A recent study by Hung et al [13] provided a comprehensive insight of the failure mechanism of bolt-bearing damage, but focused only on a single washer size in their experiments.…”
mentioning
confidence: 99%
“…Although bolt-bearing tests have been conducted by many investigators in the past [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], limited data were available to fairly assess the validity of the 3-D model and the computer code, 3DBOLT/ABAQUS. A recent study by Hung et al [13] provided a comprehensive insight of the failure mechanism of bolt-bearing damage, but focused only on a single washer size in their experiments.…”
mentioning
confidence: 99%
“…Many authors have conducted experimental studies showing that elevated temperatures reduce the strength of polymer matrix composite joints [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Additionally, a few twodimensional analysis models were developed to investigate the bearing behavior of composite joints at elevated temperatures [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly attributed to the absence of load sharing due to plastic yielding [3,4]. Baillie et al [5] suggested that all bolts in a given joint are only loaded equally at failure, while Madenci et al [6] showed that the maximum bolt hole stress occurred closest to the loaded edge. The commonly observed modes of failure in bolted composite joints are similar to the ones observed in metallic bolted joints namely: tension, cleavage, bearing and shear out.…”
mentioning
confidence: 99%